The Palgrave Handbook of Gender, Media and Communication in the Middle East and North Africa - Skalli, Loubna H.; Eltantawy, Nahed (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XXIII, 590 p. 50 illus. in color.